Reconsidering the use of cut-off scores for the Eating Disorder Examination–Questionnaire. Issue 5 (3rd September 2021) - Meule, Adrian
ABSTRACT: The Eating Disorder Examination–Questionnaire (EDE–Q) is one of the most widely used self-report measures for the assessment of eating disorder psychopathology. Numerous studies have provided norm data for different populations and suggested possible cut-off values for the EDE–Q global score that may indicate the presence of an eating disorder. This commentary argues against the unquestioned use of such cut-off scores as their application may often be unnecessary, disadvantageous, or inappropriate.